Tritrophic defenses as a central pivot of low-emission, pest-suppressive farming systems - Wyckhuys, Kris A.G.; Zhang, Wei; Colmenarez, Yelitza C.; Simelton, Elisabeth; Sander, Björn Ole; Yanhui Lu (Elsevier, 2022)
The ongoing COVID-19 pandemic has spotlighted the intricate connections between human and planetary health. Given that pesticide-centered crop protection degrades ecological resilience and (in-)directly harms human health, the adoption of ecologically sound, biodiversity-driven alternatives is imperative. In this Synthesis paper, we illuminate how ecological forces can be manipulated to bolster ‘tritrophic defenses’ against crop pests, pathogens, and weeds. Three distinct, yet mutually compatible approaches (habitat-mediated, breeding-dependent, and epigenetic tactics) can be deployed at different organizational levels, that is, from an individual seed to entire farming landscapes. Biodiversity can be harnessed for crop protection through ecological infrastructures, diversification tactics, and reconstituted soil health. Crop diversification is ideally guided by interorganismal interplay and plant–soil feedbacks, entailing resistant cultivars, rotation schemes, or multicrop arrangements. Rewarding opportunities also exist to prime plants for enhanced immunity or indirect defenses. As tritrophic defenses spawn multiple societal cobenefits, they could become core features of healthy, climate-resilient, and low-carbon food systems.